Israel : Staff Report for the 1999 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2000)
Israel is on the threshold of a marked improvement in economic performance. Passage of a revised Bank of Israel law along the lines recommended by the Levin Commission and endorsed by the Bank of Israel should be achieved as soon as possible. Continued vigilance regarding real exchange rate trends, conditions of access to international capital markets, and the health of the banking sector is essential. The government is to be commended for its success in liberalizing Israel's foreign trade and capital accounts.